Validation of integrated pest management module for major pests of Bt cotton in north-west India - ACHARYA, LICON KUMAR; BIRAH, AJANTA; KUMAR, ANOOP; KHOKHAR, M K; SINGH, S P; KUMAR, RISHI (The Indian Journal of Agricultural Sciences, 2025)
Cotton (Gossypium spp.) is widely cultivated in the north-western states of India. Although Bt cotton provides resistance to bollworms, cotton cultivation in these regions continues to face challenges from various insect pests and diseases. The increasing infestation of pink bollworm and jassids, along with the incidence of boll rot, has led to severe yield losses and an over-reliance on chemical pesticides. The present study was carried out during rainy (Kharif) season of 2022–2024 in Bhainichanderpal village, Rohtak, Haryana to conduct a Integrated Pest Management (IPM) validation trial aimed to manage key pests, particularly jassids, pink bollworm, and boll rot, while reducing chemical dependence and promoting ecological balance. The IPM interventions included timely sowing, regular pest monitoring, seed treatment with Trichoderma asperellum, installation of yellow sticky traps, use of Specialized Pheromone and Lure Application Technology (SPLAT) for pink bollworm management, and need-based application of safer pesticides. The IPM module significantly reduced green boll damage by pink bollworm (12.95% in IPM vs. 19.75% in the farmers’ practice) and minimized the incidence of boll rot (13.2% in IPM vs. 23.85% in the farmers’ practice). There was a 21.05% increase in seed cotton yield under IPM compared to the farmers’ practice, along with a higher benefit-cost ratio (2.15 in IPM vs. 1.65 in FP). Additionally, IPM led to a 33.5% reduction in pesticide applications compared to the control. These findings highlight the importance of IPM in enhancing cotton yield and profitability by reducing pesticide dependence and promoting natural enemies.